Exploring the interface between mental health provision and the benefits system: clinical psychologists' experiences of working in the context of the UK benefits system. Issue 4 (29th July 2021) - Cantrell, Erika; Weatherhead, Stephen; Higson, Hayley
Abstract : Purpose: This study aimed to explore the interaction between the benefits system and the work of clinical psychologists. The perceived impact of the benefits system on the practice of clinical psychologists and their perspectives on the role of Clinical Psychology this context were explored. Design/methodology/approach: Fifteen clinical psychologists who worked in a variety of National Health Service (NHS) settings across England were interviewed. Thematic analysis was used to identify patterns in the data. Findings: Issues relating to the benefits system were seen to increase the demand for psychological support but created barriers to engagement. Participants faced dilemmas regarding how best to practice in this context and felt uncertain of their role. Participants wanted further support and guidance to understand their role and how they could effectively support clients affected by the benefits system. Most participants interacted with the benefits system on an individual-level but believed that clinical psychologists should influence higher-level change, with adequate support and professional leadership. Originality/value: There is a paucity in research exploring the practice of mental health professionals in relation to socioeconomic influences on mental health. To the best of the authors' knowledge, this is the first study exploring the association between the work of clinical psychologists and the benefits system.